Interoception Disorder and Insular Cortex Abnormalities in Schizophrenia: A New Perspective Between Psychoanalysis and Neuroscience - Tran The, Jessica; Magistretti, Pierre J.; Ansermet, Francois (Frontiers in Psychology, 2021)
The existence of disturbances in the perception of somatic states and in the representation of the body with the presence of cœnesthetic hallucinations, of delusional hypochondriac ideas or of dysmorphophobias is a recognized fact in the psychopathology of schizophrenia. Freudian psychoanalytic theory had accorded a privileged place to the alteration of the perception of the body in schizophrenia. Freud had attributed to these phenomena a primary and prodromal role in the psychopathology of psychosis. We propose to look at this theory in a new way, starting from the perspective of recent studies about the role of the insula in the perception and representation of somatic states, since this structure has been identified as underpinning the sense of interoception. The data in the neurobiological literature about abnormalities in the insular cortex in schizophrenia has shown that insula dysfunction could constitute one of the biological substrates of disorders of body perception in schizophrenia, and could be a source of the alteration of the sense of self that is characteristic of this psychiatric pathology. Moreover, this alteration could thus be involved in the positive symptomatology of schizophrenia.